Evolutionary Dynamics and Lateral Gene Transfer in Raphidophyceae Plastid Genomes - Kim, Jong Im; Jo, Bok Yeon; Park, Myung Gil; Yoo, Yeong Du; Shin, Woongghi; Archibald, John M. (Frontiers in Plant Science, 2022)
The Raphidophyceae is an ecologically important eukaryotic lineage of primary producers and predators that inhabit marine and freshwater environments worldwide. These organisms are of great evolutionary interest because their plastids are the product of eukaryote-eukaryote endosymbiosis. To obtain deeper insight into the evolutionary history of raphidophycean plastids, we sequenced and analyzed the plastid genomes of three freshwater and three marine species. Our comparison of these genomes, together with the previously reported plastid genome of Heterosigma akashiwo, revealed unexpected variability in genome structure. Unlike the genomes of other analyzed species, the plastid genome of Gonyostomum semen was found to contain only a single rRNA operon, presumably due to the loss of genes from the inverted repeat (IR) region found in most plastid genomes. In contrast, the marine species Fibrocapsa japonica contains the largest IR region and overall plastid genome for any raphidophyte examined thus far, mainly due to the presence of four large gene-poor regions and foreign DNA. Two plastid genes, tyrC in F. japonica and He. akashiwo and serC in F. japonica, appear to have arisen via lateral gene transfer (LGT) from diatoms, and several raphidophyte open reading frames are demonstrably homologous to sequences in diatom plasmids and plastid genomes. A group II intron in the F. japonica psbB gene also appears to be derived by LGT. Our results provide important insights into the evolutionary history of raphidophyte plastid genomes via LGT from the plastids and plasmid DNAs of diatoms.